Cognitive Biases in Cannabis, Opioid, and Stimulant Disorders: A Systematic Review - Zhang, Melvyn W. B.; Ying, Jiangbo; Wing, Tracey; Song, Guo; Fung, Daniel S. S.; Smith, Helen E. (Frontiers in Psychiatry, 2018)
Background Opiates, cannabis and stimulants are highly abused and are prevalent disorders. Psychological interventions are crucial given that they help individuals maintain abstinence following a lapse or relapse into substance use. The dual-process theory has posited that whilst the repeated usage of a substance leads to increased automatic processing and increased automatic tendencies to approach substance-specific cues, in addition to the inhibition of other normal cognitive processes. Prior reviews are limited, as they failed to include trials involving participants with these prevalent addictive disorders or have not reviewed the published literature extensively. Objectives The primary aim of this review is to synthesize the evidence for attention and approach biases in opioid use, cannabis use, and stimulant use disorders. The secondary aim of the review is to determine if attentional or approach bias could be consistently detected using the different methods. Lastly, this review will narratively synthesize the evidence of possible associations between attention or approach biases and other addiction-related outcomes. Methods A search was conducted from November 2017 to January 2018 on PubMed, MEDLINE, Embase, PsycINFO, Science Direct, Cochrane Central and Scopus. Articles were included if participants had a primary diagnosis of opioid use, cannabis use, or stimulant use disorder. The selection process of the articles was in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analysis guidelines. A qualitative synthesis was undertaken. Results A total of 38 studies were identified. The main finding is the evidence that attentional and approach biases are present in the 38 studies identified, except for a single study on opioid use and stimulant use disorders. Biases were reported despite a variety of different methods being utilized. A synthesis of secondary outcome was not feasible, due to the varied outcomes reported. Conclusions Attentional and approach biases have been consistently observed in opioid use, cannabis use, and stimulant use disorders, despite a range of assessment tools being utilized in the assessment for these biases.